Pengaruh Substitusi Tepung Limbah Kubis (Brassica oleracea) Terfermentasi terhadap Kecernaan Serat Kasar dan Lemak Kasar Ternak Babi Fase Starter - Lamury, Dominikus Denri Yeski; Nalley, Wilmintje Marlene; Suryani, Ni Nengah (Animal Agricultura, 2024)
The purpose of this study was to test the effect of substitution of fermented cabbage waste flour (Brassica oleracea) on the digestibility of crude fiber and crude fat. The livestock used were 12 head of starter phase landrace pigs aged 1-2 months, with an average initial body weight of 10.7 kg (CV 15.33%). The design used was a randomized group design consisting of 4 treatments and 3 tests. Each treatment was: R0: 100% basal ration (RB) without the use of fermented cabbage waste flour (FCWF), R1: 95% RB plus 5% FCWF, R2: 90% RB plus 10% FCWF, R3: 85% RB plus 15% FCWF. The variables studied were the digestibility of crude fiber and crude fat. The results showed that the substitution of fermented cabbage waste flour had a real effect on the consumption of crude fat (P<0.05) but had an unreal effect (P>0.05) on the consumption of crude fiber, the digestibility of crude fiber and crude fat of pig livestock. The conclusion of this study is that the use of 15% fermented cabbage waste flour substitutes basal rations to increase crude fat consumption, but exerts the same influence on crude fiber consumption, crude fiber digestibility and crude fat of landrace pig livestock starter phase.